Industry of Last Resort: Negotiating Admissible Identities in “Leisurescape” - Law, Alan (Loisir et Société / Society and Leisure, 2001)
AbstractThis paper interprets Collingwood Ontario’s negotiation of “leisurescape” in the context of global economic and cultural forces centering on the production of rural places as playgrounds for the urban middle class. Host communities that articulate “leisurescape” demanded by tourist resorts may certainly negotiate economic and cultural benefits, as well as bear the costs. However, negotiation of the place of “leisurescape” in relation to other sources of community identity is mediated by the depth, and breadth of alternative sources as well as the existence of platforms upon which symbolic negotiation can take place. Located in the literatures on urban gentrification and cultural commodification, the paper follows discourse converging on three symbolic “crises” centered on the community’s definitive shipyard site. It is argued that communities are not necessarily consigned to become opaque mirrors of the tourist gaze. Rather, resort development can stimulate the conscious negotiation of community symbols, potentially capable of co-locating industry and leisurescapes.